(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s): The aim of this study was to simplify the loading dose of MgSo4 in the management of eclampsia. Materials and Methods: This cross sectional study was conducted in Eclampsia unit of Dhaka Medical College Hospital during the period from April, 2010 to October, 2010. One hundred patients who admitted in the eclampsia ward were the target population for this study.Patients were selected purposively to use either (Group A=50) 10 gm MgSO4, 4 gm IV and 6gm IM or (Group B =50) 8 gm of Nalepsin IV as loading dose. Maintenance dose were given by the same protocol in eclampsia unit of DMCH. Main outcome measures were controlling and recurrence of convulsion. Result: There was no statistically significant difference in terms of recurrent convulsion (p=0.248). There was no significant difference in live birth rate (p=0.564) and birth condition of the baby (p=0.195). But there is a significant difference in NICU transfer of the baby. Twentytwo babies in group A and 30 babies of group B were referred to NICU (p=0.042). Time required to regain consciousness was same in two groups. Maternal conditions during admission were almost same though two patients condition was very poor in group A and those two died. From group A out of 50 patients 22 developed different complications and 8 patients needed referral to ICU and that poor prognostic 2 patients died. In group B 18 patients developed different complications and 6 patients needed referral to ICU and no mother died. There was a significant difference in term of maternal complications (p =0.044) though it is not related to schedule of anticonvulsant. Conclusion: The results of loading dose of 8g of magnesium heptahydrate IV and 10g of MgSO4IV and IM for controlling convulsion in eclampsia is comparable in terms of maternal and foetal outcome. But 8g of magnesium heptahydrate IV as a loading dose is easy to administer and dose not need to dilute the injection. So for convenience of health workers this simple schedule can be introduced for controlling convulsion in eclampsia as it is easy to administer and painful intramuscular injections can be avoided. Moreover, it is more economic and the risk of toxicity is less. Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 67-73